(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: The term Spondyloarthritis (SpA) is used to describe a group of diseases with common clinical, laboratory and genetic characteristics, which may involve the axial and/or peripheral skeleton. Objectives: To study the epidemiological profile, the current clinical status of the patients and the drugs most commonly used to control the disease. Methods: Cross-sectional study of patients who were regularly followed up at the Cassiano Antônio de Moraes University Hospital (HUCAM-UFES), one of the centers participating in the prospective and observational cohort of the Brazilian Spondyloarthritis Registry (RBE). Additional data was obtained from the patients’ electronic medical records. Results: 105 patients were studied; there was a predominance of brown individuals 52 (49.5%), men (64/61%) and the average age was 49 years; with a higher prevalence of ankylosing spondylitis (62/59%), axial form (76/72.4%), with HLA-B27 positivity in 55 (52.4%) individuals. We identified 50 (47.6%) patients with csDMARDs and 87 (82.9%) with bDMARDs, with a mean ASDAS-PCR: 3.3 (± 1.8), BASDAI: 3.6 (± 2.5) and DAPSA: 21.5 (± 21.8). White color was associated with greater positivity for HLA-B27 and black color with greater disease activity by ASDAS-PCR. Conclusion: In this study, there was a predominance of men of African descent and greater axial involvement. HLA-B27 was identified as an important genetic marker associated with the patients’ phenotype. Black patients had higher activity rates compared to the other groups. Treatment with bDMARDs was predominant, with patients in disease activity, demonstrating a sample with a profile of greater severity and difficult treatment.